1979
DOI: 10.1128/iai.26.2.764-766.1979
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus infection in inbred mice

Abstract: Respiratory syncytial virus infected the nose and lungs of each of 20 strains of inbred mice, with viral titers varying 100-fold from least permissive to most permissive strains. Viral titers appeared to be under genetic control, but did not correlate with the H-2 haplotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 7 publications
4
51
0
Order By: Relevance
“…This is to our knowledge the first report of in vivo imaging of RSV replication. RSV replication was detected in the snout and lungs of living mice, as previously described 32 . Since we used 10-1,000-fold-less infectious particles per mouse than usually used 7 , these results also show how sensitive the readout is for RSV replication using the Luc assay.…”
Section: Discussionmentioning
confidence: 99%
“…This is to our knowledge the first report of in vivo imaging of RSV replication. RSV replication was detected in the snout and lungs of living mice, as previously described 32 . Since we used 10-1,000-fold-less infectious particles per mouse than usually used 7 , these results also show how sensitive the readout is for RSV replication using the Luc assay.…”
Section: Discussionmentioning
confidence: 99%
“…Coates and Chanock [64] examined several species, including four strains of inbred mice (DBA/2, BALB/c, AKR, and C3H), to determine permissive for pulmonary viral infection and found that none of those four mice developed CF antibody, but only one strain (AKR) developed neutralising antibody. Prince et al [52], Prince et al [53] found that each of 20 inbred strains, including the four tested earlier, as permissive for RSV infection in the lungs and nose. Levels of viral replication varied by two orders of magnitude from the least permissive (CBA/CaHN) to the most permissive (DBA/2N) strains, and the most permissive strain was about 100-fold less sensitive than the cotton rat [57].…”
Section: Mouse Versus Ferrets Modelmentioning
confidence: 94%
“…The genetic heterogeneity among outbred animals, the statistical insignificance of data and verification of published observations by other laboratories are not possible owing to limited number of animals, and thus raise questions about the scientific validity of these experiments. Experimental RSV infection has also been described in the owl monkey [51][52][53], rhesus monkey [49], African green monkey [54], cebus monkey [51], squirrel monkey [49], bonnet monkey [55], and baboon [56] but both purchase and maintenance costs of these species are high and handling is cumbersome, though unlike chimpanzees, these species can be used in terminal experimentation, thus allowing more detailed virological and histological studies of pulmonary RSV disease. Lack of inbreeding in these species limits other studies, and none develop clinical or radiological signs of pulmonary RSV disease, except owl monkeys that develop mild rhinorrhea.…”
Section: Inoculation Of Virus In Nasal Cavitymentioning
confidence: 99%
See 1 more Smart Citation
“…After intranasal administration, strong RSVspecific antibody responses were observed, and the animals were protected from subsequent RSV challenge (Hsu et al, 1994). Since replication in the lung only takes place in infant ferrets (Prince and Porter, 1976), their use as animal model for pneumovirus pathogenesis studies has been limited and little is known about the cellular receptors or mechanisms involved, even though ferrets reproduce the age-dependent differences in disease severity seen in humans.…”
Section: Pneumovirusesmentioning
confidence: 99%